2011
DOI: 10.1159/000330808
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Combination of Cytology and Hybrid Capture to Safely Predict the High-Grade Lesion Status of Patients Treated with Conization with Large Loop Excision of the Transformation Zone

Abstract: Objectives: This study aimed to verify whether human papillomavirus (HPV) testing after conization treatment has some potential usefulness for predicting patients’ outcome. Study Design: One hundred and twenty women were treated for HSIL by conization with large loop excision of the transformation zone (LLETZ). Cytology, colposcopy-guided biopsy, and hybrid capture 2 (HC2) HPV DNA tests were performed before the surgical procedure and every 6 months for 2 years at follow-up. Results: More than 90% of the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
1
4
0
3
Order By: Relevance
“…The results of the present study supported the use of the HC2 HPV DNA test, collected in the first post-operative assessment, as a marker of disease recurrence or a disease-free status (11). Additionally, the results demonstrated that the characterization of p16 in a well-controlled population that underwent cervix conization due to the HSIL alteration was concordant with previous results.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The results of the present study supported the use of the HC2 HPV DNA test, collected in the first post-operative assessment, as a marker of disease recurrence or a disease-free status (11). Additionally, the results demonstrated that the characterization of p16 in a well-controlled population that underwent cervix conization due to the HSIL alteration was concordant with previous results.…”
Section: Discussionsupporting
confidence: 78%
“…In our previous study, containing partial information from the present study, we identified that patients with a combination of negative cytology and negative hybrid capture test results did not exhibit high-grade lesions at the conization follow-up examination (11). The results of the present study supported the use of the HC2 HPV DNA test, collected in the first post-operative assessment, as a marker of disease recurrence or a disease-free status (11).…”
Section: Discussionmentioning
confidence: 71%
“…Most precancerous lesions arise at the transformation zone, and it has been shown that after excision of the lesion and the transformation zone a high percentage of women clear not only the lesion but also the infection, and become negative for HPV . This suggests that the HPV infection is mainly limited to the lesion and the transformation zone.…”
Section: Introductionmentioning
confidence: 99%
“…Atualmente, a IARC (Agência Internacional para Pesquisa de Câncer) divide os HPVs em de baixo risco oncogênico (HPV-6, 11, 40, 42, 43, 44, 54, 61, 70, 72 e 81) e de alto risco oncogênico (HPV- 16,18,31,33,35,39,45,51,52,56,58,59,68, 73 e 82) de acordo com a sua capacidade de gerar neoplasias malignas (14) . Os tipos HPV- 26,53,66,67,68,70, 73 e 82 são classificados como genótipos de provável alto risco (14,31,32) . (19) .…”
Section: Epidemiologia Do Hpvunclassified
“…(67) . Outro estudo de Roncaglia et al (68) avaliou se o teste de HPV (captura híbrida) após tratamento com conização em pacientes com diagnóstico de neoplasia intraepitelial cervical de alto grau (NIC II e III) tinha alguma utilidade potencial para predizer a resposta da paciente ao tratamento, isto é, se havia a presença de doença residual ou recidiva e verificaram que o teste de HPV negativo foi correlacionado com a ausência de lesão de alto grau após dois anos de seguimento pós-conização, o que fortemente sugere que um teste HPV negativo prediz a ausência de doença cervical (68) .…”
Section: Testes Para Detecção De Recidivas E Monitoramento Da Respostunclassified